Audiences vs. disinformation. An exploration during the COVID-19 pandemic in Colombia (2020)
On March 25, 2020, the Colombian government decreed mandatory preventive isolation or quarantine because of the covid-19 pandemic. In this framework, an exploratory research was conducted on the consumption habits of national news media outlets, and among other aspects, the handling of the Colombian audiences on disinformation and hoaxes to which they are exposed in instant messaging services and social networks was addressed. An online survey was applied between April and May 2020 in which 2,084 people from all regions of the country participated in total. The results show that there is concern about discerning between false and authentic news information, and about not participating in distribution chains. Even so, the implementation and permanence of media literacy strategies aimed at handling disinformation and hoaxes are still necessary. © 2020 Universidade da Beira Interior. All rights reserved.